INTELLECTUAL DEVELOPMENT OF THE SCHOOL STUDENTS WITH DIFFUSIVE CLINICALLY EUTHYROID GOITER IN THE REGIONS WITH DIFFERENT IODINE OCCURENCE - E.A. Troshina; N.M. Platonova; S.I. Solov’eva; F.M. Abdulkhabirova (Педиатрическая фармакология, 2009)
The article highlights the evaluation results of the IQ indices demonstrated by the school students, who reside in the regions with different degrees of the iodine deficiency severity and iodine provided regions. The authors performed the comparative analysis of the IQ indices among children with clinically euthyroid diffusive goiter and among children with normal sizes of the thyroid gland. The research included 260 children aged from 8 to 10 from 13 regions of the Russian Federation: 130 patients with the goiter diagnosed subject to the data of the ultrasound investigation and 130 children, who have normal sizes of the thyroid gland (reference group). The comparison groups were homogenous according to the education conditions (as only children from the city comprehensive schools took part in the research). For the evaluation of the intellectual development, authors used R. Kettell's intellect test free from the cultural impact (Сulture-Fair Intelligence Test, CFIT) — CF 2А form. Despite the fact that the average IQ indices in the group of children with goiter were slightly lower than among children with normal sizes of the thyroid gland, the researchers failed to identify statistically significant differences between the average IQ indices among children in the compared groups (р > 0,05). Both in the group of children with goiter and in the reference group, the average IQ indices fell within «the low normal» (80–89 points).Key words: iodine, hypothyroidism, IQ intellect index, children.